Kedudukan Anak Adopsi dalam Pewarisan Berdasarkan atas Hukum Adat Bali - I Gede Eka Julia Artanida wijaya (Jurnal Preferensi Hukum, 2020)
The law of inheritance is a law that regulates what should happen to the deceased person's property, in other words, it regulates the transfer of property left by the deceased to the heir. In principle, only rights and obligations in the field of property law can be inherited, and it does not include rights and obligations in the field of law that cannot be inherited, such as work agreements, employment relationships, individual membership, and authorizations. This research was conducted with the aim of describing the rights and obligations of an adopted child in inheriting property by the adopted parent and the position of the adopted child in inheriting property by the adopted parent. This research was conducted using empirical legal research methods. The results of this study indicated that adopted children in Bali are entitled to receive an inheritance from their adopted parents as well as their biological parents. This is known as ma’bubun dua ma’saruran patomali. Its meaning has two kiblat oase, that is to be able to be given an inheritance from adoptive parents as well as biological parents. On the other hand, the adopted child is obliged to maintain and establish family relationships as harmonious as possible, and carry out or replace the role or obligation of the adopted father/mother to the duties of the area where he lives (local community). In addition, the position of the adopted child in the inheritance of the property by the adopted parent is equal to or completely the same when compared to the biological child. Therefore, the adopted child is also entitled to inherit the inheritance of the adopted parent.